Tocilizumab for treating mevalonate kinase deficiency and TNF receptor-associated periodic syndrome: a case series and literature review - Yandie Li; Meiping Lu (Pediatric Rheumatology Online Journal, 2024)
Abstract Background Mevalonate kinase deficiency (MKD) and TNF receptor-associated periodic syndrome (TRAPS) are categorized as systemic autoinflammatory diseases (SAIDs), which are rare diseases characterized by early onset, severe conditions, and challenging diagnosis and treatment. Although different SAIDs have varying standard treatments, some SAIDs are poorly controlled after routine treatment, seriously affecting the growth and development of children and their quality of life. This study aims to provide more treatment strategies for SAIDs. Case presentation We present two Chinese patients with MKD and TRAPS who were resistant to TNF- (tumor necrosis factor-) α blockade. After using etanercept, baricitinib, and glucocorticoid, patients with MKD and TRAPS still had periodic fever and rash. Due to the unavailability of IL-1 antagonists in the Chinese Mainland, we started administering intravenous tocilizumab (TCZ) at a dosage of 240 mg every three weeks. They had not experienced fever or rash after receiving one or two doses of TCZ. Before treatment with TCZ in the MKD patient, white blood cell (WBC) count, and TNF-α level were normal, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) increased significantly, and IL-6 increased slightly. After treatment with TCZ, ESR and CRP levels returned to normal; however, IL-6 increased occasionally. In the TRAPS patient, ESR, CRP, WBC, IL-6, and TNF-α levels were increased significantly. After TCZ treatment, ESR, CRP, WBC, IL-6, and TNF-α levels returned to normal. The two patients were treated with TCZ for more than six months and achieved clinical and serological remission. Furthermore, they had no adverse reactions after injection of TCZ. Conclusion In the absence of IL-1 antagonists in mainland China, tocilizumab emerges as an alternative drug in SAIDs that are resistant to TNF-α blockade.